Performance analysis of a network coding scheme based on orthogonal process - Zu-fan ZHANG; Chun-ling PENG; Jing YANG; Xiao-rong JING (Tongxin xuebao)
Combining the orthogonal low-frequency subcarrier processing, a network coding scheme based on orthogonal process (NCOP) was proposed for effective transmission in multi-user multi-relay networks. It makes the data orthogonal before transmission,and decodes the data utilizing the characteristics of orthogonality, so that further reduces the system outage probability and develops the diversity order. The system outage performance and average bit error rate was ana-lyzed by theoretical analysis. Analysis and simulation results show that the system performance of the proposed NCOP outperforms linear network coding while applying in multi-user cooperative networks.